Evaluation of the impact of guideline communication from the Centers for Disease Control and Prevention and the Centers for Medicare and Medicaid Services among US healthcare providers: COVID‐19 prevention counselling guidance - Melanie M. Taylor; Arkaprava Deb; Bernita Frazier; James Reiss Lueken; Mansi Das; Joanna Molke; Erin Fitzgerald; Tom Ullian; Ridhu Nair; Marion Couch; Caitlin Turbyfill; Libby Horter; et al. (Wiley, 2023)
Abstract Aim To evaluate healthcare provider awareness and uptake of the Centers for Medicare & Medicaid Services (CMS) billing for coronavirus disease 2019 (COVID‐19) prevention counselling and the delivery of prevention counselling to patients awaiting severe acute respiratory syndrome coronavirus 2 test results. Design Cross sectional survey of US‐based healthcare providers in February 2021. Methods Analysis of associations with healthcare provider‐reported awareness of CMS prevention counselling guidance and billing with provider type, specialty, and work setting. Results A total of 1919 healthcare providers responded to the survey. Overall, 38% (726/1919) of providers reported awareness of available CMS reimbursement for COVID‐19 patient counselling and 29% (465/1614) of CMS billing‐eligible providers reported billing for this counselling. Among physicians, those aware of CMS guidance were significantly more likely to bill (58%) versus those unaware (10%). Among RNSights respondents eligible for CMS billing (n = 114), 31% of those aware of the guidance reported billing as compared to 0% of those not aware.